Person Job Fit Terhadap Employee Performance Dimediasi Work Life Balance Dan Job Involment - Welni Fitrha Nurlya Manda Lubis; Muhammad Irfan Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of person job fit and work life balance, the influence of person job fit and job involvement. influence of work life balance and employee performance. the influence of job involvement and employee performance. The influence of person job fit and employee performance. The influence of person job fit and employee performance is mediated by work life balance. The influence of person job fit and employee performance is mediated by job involvement. This research adopted an associative research design with a sample of 100 respondents who were employees of PT. TELKOM Witel Medan. The data collection technique involves a list of statements such as a questionnaire, and data analysis using Path Analysis. The Partial Least Square (SmartPLS) application tests the seven hypotheses proposed in this research. The research findings show that person job fit and work life balance have no effect, the influence of person job fit and job involvement is significant. Work life balance and employee performance have a positive and significant influence. Job involvement and employee performance have a positive and significant effect. Person job fit and employee performance have a positive and significant effect. Person job fit and employee performance are mediated by work life blank which has no effect or does not mediate. Meanwhile, person job fit and employee performance, mediated by job involvement, have a positive and significant effect. This research offers important lessons for thinkers in management, human resources (HR), person job fit and employee performance. However, companies in the telecommunications sector must be aware of the important role that person job fit plays in improving work-life balance and employee performance as well as the role of job involvement that can be paid attention to and considered. This study provides us with a comprehensive review of the various Work Life Balance studies conducted by state-owned telecommunications companies to date and their possible impact on various organizational outcomes. Keywords: Person Job Fit, Employee Performance, Work Life Balance, Job Involvement